Pengaruh Latihan Plyometric dan Plyometric + (Duel) terhadap Kekuatan dan Explosive Power Otot Tungkai dan Lengan pada Siswa Dayung dan Jiu Jitsu Ijukai Kabupaten Bandung Barat - Franky Alfonsius Pattisina; Ronald Hamidie; Mulyana Mulyana (Journal on Education, 2023)
Sports in the modern era demand competitive improvement from athletes and coaches, in this case the development of sports requires technology for training to be continuously improved. One of them is the development of highly active sports games with changes in speed including jumps, and active use of muscles. For this reason, quality training is needed in order to achieve the desired results. Through plyometric and plyometric + (DUEL) training is expected to be able to improve the ability of the body's work system. So as to achieve predetermined targets, training is a very important factor in competitive sports. This study aims to determine whether there is an effect of plyometric and plyometric + (DUEL) training on arm and leg grip strength and explosive power of leg muscles and explosive power of arm muscles in West Bandung Regency Rowing and Jiu Jitsu Ijukai Students. The research method used is experiment and this research design uses quasi-experiment design. While the experimental design model used is a non-equivalent control group design. With data collection techniques using purposive sampling with a sample size of 30 students rowing and Jiu Jitsu Ijukai West Bandung Regency. The overall research result is that there is have a significant effect from plyometric and plyometric + (DUEL) training on arm and leg grip strength as well as explosive power of leg muscles and explosive power of arm muscles in Students Rowing and Jiu Jitsu Ijukai West Bandung Regency.